Garcilaso de la Vega: maestro de la Historia - Kagan, Richard L. (2020)
This article addresses the figure of Garcilaso de la Vega as a historian and the influence he exerted over the historiographic writing of his contemporaries, concretely the one of the general chronicler of the Indies, Pedro de Valencia. Thereby, this study will discuss the principal requirements Garcilaso considered when writing history: to tell the truth, to possess reliable sources and to transmit the voices of those who were born in the place one is writing about. These guides, in resonance with personal and political calculations, would eventually provoke Valencia to refrain himself from finishing his investigation of the history of the conquest of Chile.